The role of green innovation in the effect of corporate social responsibility on firm performance - Maya Novitasari; Zeplin Jiwa Husada Tarigan (Economies, 2022)
Indonesia's government policy recommends that medium and large companies carry out corporate social responsibility programs. These programs provide sustainability for the company because they can involve community social relations, economic growth, and increasing environmental awareness. This study aimed to test corporate social responsibility on firm performance with green innovation as a mediation. This study used PROPER companies in 2015-2019, which were chosen using a purposive sampling method involving annual reports and financial reports, yielding 253 companies as a sample. Data were obtained from the Indonesia Stock Exchange and tested using STATA. This study indicates that corporate social responsibility can increase green innovation in companies with the stability of environmentally friendly materials, emission reductions for the surrounding community, and saving energy use. Corporate social responsibility has a positive effect on firm performance because the company has maintained the continuity of the process. After all, it has a harmonious relationship with the community. Furthermore, green innovation positively affects firm performance because the company can reduce energy use and utilize environmentally friendly resources. Therefore, green innovation can mediate the influence of corporate social responsibility and firm performance. This research contributes to senior managers who are part of their company's top management to understand the critical role of corporate social responsibility in maintaining the company's sustainability by paying attention to the part of the company's environment and implementing government regulations. Corporate social responsibility can maintain good stakeholder relations and increase green innovation and firm performance. Theoretical contributions can enrich research related to the context of sustainable performance.
Keywords: 330; firm performance; corporate social responsibility; green innovation